Additional Value of 18F-FDOPA Amino Acid Analog Radiotracer to Irradiation Planning Process of Patients With Glioblastoma Multiforme - Sipos, David; László, Zoltan; Tóth, Zoltan; Kovács, Peter; Tollár, Jozsef; Gulybán, Akos; Lakosi, Ferenc; Repa, Imre; Kovács, Arpad (Frontiers in Oncology, 2021)
Purpose: To investigate the added value of 6- (18F] -fluoro-L-3,4-dihydroxyphenylalanine (FDOPA) PET to radiotherapy planning in glioblastoma multiforme (GBM). Methods: From September 2017 to December 2020 17 patients with GBM received external beam radiotherapy up to 60 Gy with concurrent and adjuvant temozolamide. Target volume delineations followed the European guideline with 2 cm safety margin clinical tarteg volume (CTV) around the contrast enhanced lesion+resection cavity on MRI gross tumor volume (GTV). All patients had FDOPA hybrid PET/MRI followed by PET/CT before radiotherapy planning. PET segmentation followed international recommendation: T/N 1.7 (BTV1.7) and T/N 2 (BTV2.0) SUV thresholds were used for biological target volume (BTV) delineation. For GTV-BTVs agreements 95% of the Hausdorff distance (HD95%) from GTV to the BTVs were calculated, additionally BTV portions outside of the GTV and coverage by the 95% isodose contours were also determined. In case of recurrence, the latest MR images were co-registered to planning CT to evaluate its location relative to BTVs and 95% isodose contours. Results: Average (range) GTV, BTV1.7 and BTV2.0 were 46.58 (6-182.5), 68.68 (9.6-204.1), 42.89 (3.8-147.6) cm3 respectively. HD95% from GTV were 15.5 mm (7.9-30.7 mm) and 10.5 mm (4.3-21.4 mm) for BTV1.7 and BTV2.0 respectively. Based on volumetric assessment 58.8% (28-100%) of BTV1.7 and 45.7% of BTV2.0 (14-100%) were outside of the standard GTV, still all BTVs were encompassed by the 95% dose. All recurrences were confirmed by follow-up imaging, all occurred within PTV, with an additional outfield recurrence in a single case, which was not DOPA positive at the beginning of treatment. Good correlation was found between the mean and median values of PET/CT and PET/MRI segmented volumes relative to corresponding brain accumulated enhancement (r=0.75; r=0.72). Conclusion: 18FFDOPA PET resulted in substantial larger tumor volumes compared to MRI, however its added value is unclear as vast majority of recurrences occurred within the prescribed dose level. Use of PET/CT signals proved to be feasible in the absence of direct segmentation possibilities of PET/MR in TPS. The added value of 18FFDOPA may be better exploited in the context of integrated dose escalation